2004
DOI: 10.1109/tsmcc.2004.826273
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Language for Human–Robot Dialogs

Abstract: Report Documentation PageForm Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(90 citation statements)
references
References 27 publications
0
90
0
Order By: Relevance
“…The notion of spatial description clauses is influenced by many similar formalisms for reasoning about the semantics of natural language directions [7], [8], [9], [10], [11], [12]. The structure of the spatial description clause builds on the work of Landau and Jackendoff [13], and Talmy [14], providing a computational instantiation of their formalisms.…”
Section: Related Workmentioning
confidence: 99%
“…The notion of spatial description clauses is influenced by many similar formalisms for reasoning about the semantics of natural language directions [7], [8], [9], [10], [11], [12]. The structure of the spatial description clause builds on the work of Landau and Jackendoff [13], and Talmy [14], providing a computational instantiation of their formalisms.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work that has investigated the use and representation of spatial language in human-robot interaction (HRI) includes the work of Skubic et al [9], who demonstrated a robot capable of understanding and relaying static spatial relations in natural language instruction and production tasks. Computational field models of static relations have also been used in systems for object pick-and-place tasks on a tabletop [8], and for visually situated dialogue [11].…”
Section: Related Workmentioning
confidence: 99%
“…When human-robot teams perform operational tasks, such as construction, understanding and communicating spatial dialogue plays a significant role [8]- [10]. In particular, when humans and robots work in a shared environment, robots must be able to understand how humans perceives space and the relative positions of objects around them.…”
Section: ) Spatial Reasoning Agentmentioning
confidence: 99%